Instrument Adaptation, Modification, and Validation for Cultural Beliefs About Colorectal Cancer Screening Among Korean Americans. Issue 3 (May 2018) - Lee, Shin-Young; Lee, Eunice E.; Aranda, Frances
Abstract : Background: Studies on colorectal cancer (CRC) screening among Korean Americans (KAs) lack culturally sensitive, reliable, and validated belief scales. Objective: The purpose of this study was to adapt, modify, and validate instruments measuring cultural beliefs (physical space, health temporal orientation, personal control, colon cancer fatalism, and health fatalism) about CRC screening in KAs. Methods: In phase I, instrument adaptation and modification (translation from English into Korean, individual interviews using cognitive interviewing, and expert reviews) were used to make existing cultural beliefs instruments culturally appropriate for KAs. In phase II, instrument validation (pilot test and cross-sectional survey) was used to examine the psychometric properties of the instrument among 202 KAs. Results: Construct validity and reliability of the final Korean version of the instruments were examined using exploratory and confirmatory factor analyses and internal consistency reliability. Exploratory factor analysis using all of the cultural beliefs items resulted in 5 factors accounting for 46.55% of the variance. Factor loadings were greater than 0.40 for most items to be added to the scales reflecting Korean cultural perspectives. Cronbach's α s for all the cultural beliefs subscales were greater than .70. Conclusions: Findings from this study show that KAs have unique cultural beliefs that should be reflected in the instruments used for CRC screening research with this population. Implications for Practice: The revised instrument could be useful in accurately measuring cultural beliefs among KAs and in developing culturally sensitive interventions to increase CRC screening behaviors among KAs.